Reliability, Validity, and Measurement Invariance of the General Anxiety Disorder Scale Among Chinese Medical University Students - Zhang, Chi; Wang, Tingting; Zeng, Ping; Zhao, Minghao; Zhang, Guifang; Zhai, Shuo; Meng, Lingbing; Wang, Yuanyuan; Liu, Deping (Frontiers in Psychiatry, 2021)
Background: Medical students are affected by high levels of general anxiety disorder. However, few studies have specifically focused on the applicability of universal anxiety screening tools in this sample. This study was aimed to evaluate the psychometric property of the 7-item Generalized Anxiety Disorder Scale (GAD-7) among Chinese medical university students. Methods: A questionnaire survey was conducted among 1021 medical postgraduates from six polyclinic hospitals. Internal consistency and convergent validity of the GAD-7 were evaluated. Factor analyses were used to test the construct validity of the scale. An item response theory (IRT) framework was used to estimate the parameters of each item. Multi-group confirmatory analyses and differential item function analyses were used to evaluate the measurement equivalence of the GAD-7 across age, gender, educational status, and residence. Results: Cronbach’s α coefficient was 0.93 and the intraclass correlation coefficients ranged from 0.71 to 0.87. The GAD-7 summed score was significantly correlated with measures of depression symptoms, perceived stress, sleep disorders, and life satisfaction. Parallel analysis and confirmatory factor analysis supported the one-factor structure of the GAD-7. Seven items showed appropriate discrimination and difficulty parameters. The GAD-7 showed good measurement equivalence across demographic characteristics. The total test information of the scale was 22.85, but the test information within the range of mild symptoms was relatively low. Conclusions: The GAD-7 has good reliability, validity, and measurement invariance among Chinese medical postgraduate students, but its measurement precision for mild anxiety symptoms is insufficient.